Students’ metacognitive skill in mathematics learning with Cabri Geometry II Plus - Rahmah Johar; Khalisna Khalisna; Taufik Fuadi Abidin (Proceedings of AICS - Social Sciences, 2013)
Metacognitive skill is the awareness of one's thinking about the thinking process itself, whereas consciousness is the awareness of one's thinking about what to do. The subjects for this research were five students from class VII-1 SMP 1 Banda Aceh. Research data collection used the sheet metacognitive questions. Data were analyzed descriptively to interpret students' metacognitive skills in learning how to use Cabri Geometry II Plus software. The results showed that the metacognitive abilities of students increased from the first meeting to the fourth meeting.Keywords: Metacognitive, Cabri Geometry II Plus